Structural Model for Viscoelastic Properties of Pericardial Bioprosthetic Valves. Issue 6 (30th March 2018) - Rassoli, Aisa; Fatouraee, Nasser; Guidoin, Robert
Abstract: The benefit of bioprosthetic aortic valve over mechanical valve replacements is the release of thromboembolism and digression of long‐term anticoagulation treatment. The function of bioprostheses and their efficiency is known to depend on the mechanical properties of the leaflet tissue. So it is necessary to select a suitable tissue for the bioprosthesis. The purpose of the present study is to clarify the viscoelastic behavior of bovine, equine, and porcine pericardium. In this study, pericardiums were compared mechanically from the viscoelastic aspect. After fixation of the tissues in glutaraldehyde, first uniaxial tests with different extension rates in the fiber direction were performed. Then, the stress relaxation tests in the fiber direction were done on these pericardial tissues by exerting 20, 30, 40, and 50% strains. After evaluation of viscoelastic linearity, the Prony series, quasilinear viscoelastic (QLV) and modified superposition theory were applied to the stress relaxation data. Finally, the parameters of these constitutive models were extracted for each pericardium tissue. All three tissues exhibited a decrease in relaxation rate with elevating strain, indicating the nonlinear viscoelastic behavior of these tissues. The three‐term Prony model was selected for describing the linear viscoelasticity. Among different models, the QLV model was best able to capture the relaxation behavior of the pericardium tissues. More stiffness of porcine pericardium was observed in comparison to the two other pericardium tissues. The relaxation percentage of porcine pericardium was less than the two others. It can be concluded that porcine pericardium behaves more as an elastic and less like a viscous tissue in comparison to the bovine and equine pericardium.